Crack nucleation and elastic / plastic deformation of TiAl alloys investigated by in-situ loaded atomic force microscopy - Iqbal, Farasat; Pyczak, Florian; Neumeier, Steffen; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2017)
The crack propagation mechanisms of gamma-titanium aluminides with fully lamellar microstructure have been studied using in-situ deformation in the Atomic Force Microscope (AFM). AFM demonstrated the unique capability to detect elastic as well as plastic deformation during in-situ tests from topography changes on the surface. It was found that the crack nucleation, which can occur at gamma/gamma and alpha 2/y interfaces as well as inside the gamma-phase, is always preceded by strong local elastic deformation. No cracking inside the alpha 2-phase was observed. The elastic and plastic deformation was confined inside the gamma-phase and especially pronounced near interfaces which can be explained by the differences of the elastic and plastic deformation behavior of the gamma-and alpha 2-phase.
Keywords: TiAl; Crack nucleation; In-situ observation; AFM; Elastic/plastic deformation

Eu2+ and Eu3+ based "concentrated phosphors" as converters for UV LED light: two approaches and two new examples - Batentschuk, Miroslaw; Geisler, R.; Hum, Jasmin; Iqbal, Farasat; Meister, Frank; Osvet, Andres; Stiegelschmitt, Alfons; Winnacker, Albrecht (Applied Physics B-Lasers and Optics, 2012)
The absolute majority of phosphors are composed of a host lattice and some percentage of an activator. At higher activator concentrations the concentration quenching occurs. However, there are phosphors in which only minor quenching of the emission occurs with increasing of the activator content. Based on the existence of two different valence states of the Eu ion (2+ and 3+), two approaches for the development of "concentrated phosphors", i.e. light emitting materials in which the activator ion is a main part of the crystal lattice, are discussed. In both approaches, reduced energy migration leading to the luminescence quenching is considered as a main condition to reach a high quantum efficiency of a concentrated phosphor. Two kinds of phosphors-Eu2+-doped alumosilicate and Eu3+-doped oxyfluoride-are used as an experimental basis for this discussion. Starting from the stoichiometric Ca1-x Eu-x(2+) A1(2)si(2)O8 anorthite and Eu3+OF oxyfluorides, the non-stoichiometric powders with Eu-0.92(2+) A1(1.76)Si(2.24)O(8), Eu3+(O, F)(2,35) and Eu3+(O, F)(2,16) compositions were synthesized by a solid state reaction and investigated. It was shown that-in spite of the almost 100% Eu concentration-light converters with high quantum efficiency of more than 45% can be realized. A possible application of these materials as UV LED light converters for white light emitting diodes are discussed as well.

In situ micro-cantilever tests to study fracture properties of NiAl single crystals - Iqbal, Farasat; Ast, Johannes; Göken, Mathias; Durst, Karsten (Acta Materialia, 2012)
In situ micro-cantilever tests were carried out to determine the anisotropic fracture toughness of NiAl single crystals. Notched micro-cantilever beams with a beam length of 8 extgreekmm, 1.5 extgreekmm thickness and 1.8 extgreekmm width were milled in so-called ``hard'' and ``soft'' orientations of NiAl using a focused ion beam. These cantilevers were loaded in situ with the help of a cantilever-based nanoindenter mounted inside a scanning electron microscope. A fracture toughness of 3.52 ± 0.29 MPa m1/2 was obtained for the ``soft'' orientation and 5.12 ± 0.50 MPa m1/2 for the ``hard'' orientation, which is in good agreement with literature values on the fracture toughness of macroscopic NiAl specimens. Furthermore, nanoindentations were performed for studying the size effects occurring at small length scales for both orientations. The applicability of the small sample geometries for testing the fracture toughness is finally discussed in terms of size effects in the flow stress of the material due to dislocation nucleation and strain gradients at the crack tip.
WW1::933

Microstructure development and hardness of a powder metallurgical multi phase γ-TiAl based alloy - Schloffer, Martin; Iqbal, Farasat; Gabrisch, Heike; Schwaighofer, Emanuel; Schimansky, Frank-Peter; Mayer, Svea; Stark, Andreas; Lippmann, Thomas; Göken, Mathias; Pyczak, Florian; Clemens, Helmut (Intermetallics, 2012)
WW1::941

Microstructure development and hardness of a powder metallurgical multi phase γ-TiAl based alloy - Schloffer, Martin; Iqbal, Farasat; Gabrisch, Heike; Schwaighofer, Emanuel; Schimansky, Frank-Peter; Mayer, Svea; Stark, Andreas; Lippmann, Thomas; Göken, Mathias; Pyczak, Florian; Clemens, Helmut (Intermetallics, 2012)
Keywords: A. Titanium aluminides; C. Powder metallurgy; D. Microstructure; B. Grain growth; B. Phase transformation